Serum polychlorinated biphenyl (PCB) levels and risk of testicular germ cell tumors: A population-based case-control study in Connecticut and Massachusetts. (15th March 2021) - Cheng, Zhiyuan; Zhang, Xichi; Bassig, Bryan; Hauser, Russ; Holford, Theodore R.; Zheng, Elizabeth; Shi, Dian; Zhu, Yong; Schwartz, Stephen Marc; Chen, Chu; Shi, Kunchong; Yang, Bo; et al.
Abstract: The incidence rate of testicular germ cell tumors (TGCT) has continuously increased in Western countries over the last several decades. Some epidemiologic studies have reported that the endocrine disrupting polychlorinated biphenyls (PCBs) in serum may be associated with TGCT risk, but the evidence is inconsistent. Our goal was to investigate whether serum levels of PCBs are associated with the increase of TGCT risk. We conducted a population-based case-control study of 308 TGCT cases and 323 controls, all residents of Connecticut and Massachusetts. Serum levels of 56 PCBs congeners were measured using gas chromatography and unconditional logistic regression model was used to evaluate the risk of TGCT associated with total PCBs exposure, groups of PCBs categorized by Wolff's functional groups, and individual PCB congeners. The results showed that there was no association between total serum levels of PCBs and risk of TGCT overall (quartile 4 (Q4) vs. quartile 1 (Q1) odds ratio (OR) and 95% confidence interval (C.I.) = 1.0 (0.6–1.9), ρ trend = 0.9). However, strong positive association was observed between total serum levels of Wolff's Group 1 (potentially estrogenic) PCBs and risk of overall TGCT (Q4 vs. Q1 OR = 2.5, 95% CI = 1.3–4.7, ρ trend <0.05) as well as seminoma and non-seminoma subtypes. Wolff's Group 1 PCB congeners that showed an increased risk of TGCT included: 25, 44, 49, 52, 70, 101, 174, and 201/177. Considering the continuing increase of TGCT, these associations should be replicated in different populations with larger sample size. Graphical abstract: Image 1 Highlights: PCBs biological-activities on risk of testicular germ cell tumor were different. High exposure of estrogenic PCBs group associated with the risk of testicular germ cell tumor. This association was observed in both seminoma- and non-seminoma-cancer group.